Implementation of Child-Friendly School Management: A Student-Centered Islamic Education Strategy - Mulyati, Sri Entang; Susanah, Herma; Hartati, Iis; Puspita, Devi Hadi; Iskandar, Sofyan (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2025)
This research aims to analyze the implementation of the Child-Friendly School (CFS) management strategy in elementary schools across Bandung City, emphasizing leadership roles, school culture, teacher competency enhancement through training, and parental engagement in fostering a safe, inclusive, and character-based learning environment. A descriptive qualitative approach was employed, utilizing data collection techniques such as observation, interviews, and document analysis in four elementary schools within Bandung City. The study found that the success of CFS implementation depends significantly on the principal’s ability to establish a shared vision, encourage collaboration among all school members, and ensure consistency in students’ character development. Nevertheless, the implementation still faces several challenges, including limited resources, insufficient monitoring, and policy misalignment among institutions. In general, the findings indicate that the management strategy of Child-Friendly Schools in Bandung is developing positively toward creating safe, participatory, and child-centered educational environments.